2020
DOI: 10.1088/1755-1315/476/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability assessment of building material against river flood water: case study in Malaysia

Abstract: Flood risk is increasing in Malaysia specifically around river which influencing of climate change. The aim of this study is assessing the vulnerability of building materials by revealing the degree of loss for each structure. There are most five common materials has been assessing namely: brick, concrete block, steel wall panels, wooden wall and precast concrete framing. This research was conducted on 110 buildings, to record detailed attributes of each building in the city of Kuantan. Afterwards, the intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The consolidation of buildings and its implications on flood exposure is still poorly explored in the Sahel. However, in a broader context, the water effects on buildings after a flood event is fairly recognized [39,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consolidation of buildings and its implications on flood exposure is still poorly explored in the Sahel. However, in a broader context, the water effects on buildings after a flood event is fairly recognized [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…The second gap concerns the durability of houses in the event of flooding. Currently, the focus is mainly on the precariousness of urban construction [36][37][38][39], but less on consolidation [40] in the rural context, which increases the capital exposed to flooding. Once again, here, it is essential to know the characteristics of the housing stock in order to identify the retrofitting measures that can make buildings more resistant to water [41].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the two approaches are summarised in Table 3. The studies of [42,46,50,51,57] are examples of the studies reviewed based on the empirical approach, while the studies of [35,[43][44][45] are few examples reviewed based on the synthetic approach. Nofal and van de Lindt [36] and Shrestha et al [10] combined both approaches in their studies.…”
Section: Approaches To Microscale Flood Damage Assessmentmentioning
confidence: 99%
“…Romali and Yusop [51] developed a flood damage function model for Kuantan, Malaysia, using interview survey data. Balasbaneh et al [50] also assessed the vulnerability of building materials by revealing the degree of loss for five structural types. The results of this study revealed that an increase in flood depth leads to an increase in damage to walls made from wood.…”
Section: Empirical Approachmentioning
confidence: 99%
“…Floods cause loss of life and destruction of properties [1]. Fig 1(a) shows the number of natural disasters that occurred in Asia from 1997 to 2014 [2]. Human activities of deforestation and urban land use are causing climate change with changes in flood trends [3].…”
Section: Introductionmentioning
confidence: 99%